2008
DOI: 10.1016/s1472-6483(10)60414-2
|View full text |Cite
|
Sign up to set email alerts
|

Prospectively randomized controlled trial of PGS in IVF/ICSI patients with poor implantation

Abstract: This randomized, controlled trial verifies whether patients with recurrent failed implantation benefit from preimplantation genetic diagnosis for aneuploidy, as compared with conventional assisted reproduction treatment procedures. Two hundred patients with recurrent failed implantation were randomized into two groups. A total of 139 patients underwent ovarian stimulation, and preimplantation genetic screening was performed in 72 patients. Analysis of chromosomes X, Y, 13, 16, 18, 21 and 22 was carried out usi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
55
2
5

Year Published

2010
2010
2021
2021

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 107 publications
(63 citation statements)
references
References 32 publications
1
55
2
5
Order By: Relevance
“…Contrary to expectation, results from numerous studies did not show that the PGS-FISH was capable of improving live birth rates in patients of advanced maternal age, with recurrent implantation failure or repeated pregnancy loss [35][36][37][38][39][40][41][42][43][44][45][46]. This is because FISH screening does not make it possible to test for all 23 chromosome pairs.…”
Section: Time Lapse Monitoringmentioning
confidence: 83%
“…Contrary to expectation, results from numerous studies did not show that the PGS-FISH was capable of improving live birth rates in patients of advanced maternal age, with recurrent implantation failure or repeated pregnancy loss [35][36][37][38][39][40][41][42][43][44][45][46]. This is because FISH screening does not make it possible to test for all 23 chromosome pairs.…”
Section: Time Lapse Monitoringmentioning
confidence: 83%
“…54 Son yapılan randomize kontrollü çalışmalarda TİB olan hastalarda PGT'nin IVF sonrası implantasyon oranlarını artırmadığı, hatta canlı doğum oranlarının PGS grubunda daha az olduğu sonucuna varılmış-tır. 55 Biyopsi sırasında embriyoya verilen hasar, mozaik embriyoların varlığı ve "fluorescence in situ hybridization (FISH)" ile sınırlı sayıda kromozomun incelenmesi bu durumdan sorumlu olabilir. Amerika Üreme Derneği (ASRM) ve Avrupa İnsan Üremesi ve Embriyoloji Derneği, ileri maternal yaş, TİB ya da tekrarlayan gebelik kaybı olan hastalarda PGT'nin canlı doğum oranlarını artırmadığı sonucuna varmışlardır.…”
Section: Sperm Dna Fragmantasyonuunclassified
“…This work was based on the theoretical premise of PGS without the support of randomised controlled trials (RCTs). All recent RCTs using cleavage stage biopsy followed by FISH analysis showed no improvement in delivery rates after PGS with some even suggesting adverse outcomes (Staessen et al 2004;Mastenbroek et al 2007;Blockeel et al 2008;Hardarson et al 2008;Mersereau et al 2008;Debrock et al 2010). The largest of these trials included over 200 patients in each of the experimental arms (control and treatment groups) and concluded that PGS resulted in a reduced delivery rate following IVF (Mastenbroek et al 2007).…”
Section: What We Have Learnt From Pgs Thus Far?mentioning
confidence: 99%